A systems toxicology approach reveals the Wnt-MAPK crosstalk pathway mediated reproductive failure in Caenorhabditis elegans exposed to graphene oxide (GO) but not to reduced graphene oxide (rGO). Issue 1 (2nd January 2017) - Chatterjee, Nivedita; Kim, Youngho; Yang, Jisu; Roca, Carlos P.; Joo, Sang-Woo; Choi, Jinhee
Abstract: The potential hazards of graphene nanomaterials were investigated by exposing the nematode Caenorhabditis elegans to graphene oxide (GO) and reduced graphene oxide (rGO). The underlying mechanisms of the nano–bio interaction were addressed with an integrated systems toxicology approach using global transcriptomics, network-based pathway analysis, and experimental validation of the in-silico -derived hypotheses. Graphene oxide was found to reduce the worms' reproductive health to a greater degree than rGO, but it did not affect survival (24 h endpoint). Comparative analysis of GO vs. rGO effects found that the wingless-type MMTV integration site family (Wnt) pathway and the mitogen-activated protein kinase (MAPK) pathway were evoked in GO- but not in rGO-exposed worms. We therefore hypothesized that crosstalk between the Wnt and MAPK pathways is responsible for C. elegans ' reproductive sensitivity to GO exposure. By targeting the individual components of the Wnt-MAPK crosstalk pathway (with qPCR gene expression and mutant reproduction analysis), we found a signaling cascade of MOM-2 → MOM-5 → MOM-4 → LIT-1 → POP-1 → EGL-5. Specifically, the activation of POP-1 (the TCF protein homolog) and subsequent repression of the Wnt/β-catenin target gene (EGL-5), analyzed with target-gene-specific RNAi in POP-1 mutant [ pop-1(q645) ] worms, were the central mechanisms of reduced reproductive potential in the worms exposed to GO. Our results highlight the distinct biological and molecular mechanisms of GO and rGO exposure and the role of Wnt-MAPK pathway crosstalk in regulating GO-induced reproductive failure in in vivo systems, and they will contribute to the development of efficient and innocuous graphene applications as well to improvements in mechanism-based risk assessment.